Analisis Kadar Kafein dalam Kopi Bubuk Lokal yang Beredar di Kota Palu - Suwiyarsa, I Nyoman; Nuryanti, Siti; Hamzah, Baharuddin (Universitas Tadulako, 2018)
Analysis of caffeine level in local coffee powder that circulates in Palu city have been done. The purpose of this study was to determine the level of caffeine in local coffee powder, which is engaged in several markets in the city of Palu. Levels of caffeine in the study will be compared with the standard caffeine content according to the SNI 01-3542-2004, i.e. 0.45-2% w/w. The method used for qualitative analysis was the thin layer chromatography and for quantitative analysis was using UV-Vis spectrophotometry. The results of qualitative analysis of six local coffee powders A, B, C, D, E, and F showed each a Rf value between 0.32 to 0.40. Levels of caffeine (per 1 g of coffee powder) quantitatively ranging from brand samples A to F were 0.83, 2.06, 1.60, 2.63, 1.29, and 1.72%, respectively, percent level of caffeine of six samples of local powdered coffee, samples A, C, E and F in terms of SNI 01-3542-2004 were between 0.45-2.00% (w/w), while sample B and sample D exceeds 2% were 2.06% and 2.63%.